The intention of university students to donate at zakat institution through digital payment - Rakhmawati, Rakhmawati; Rizky, Ayu Winda (Universitas Islam Indonesia, 2023)
IntroductionTechnological developments have led to several changes, one of which is the massive use of digital payments as a payment method. LAZIS Unisia has the potential to raise funds from stakeholders, including lecturers, students, alumni, and partners.ObjectivesThis study analyzes factors influencing university students' intention to donate through digital payments at LAZIS Unisia. MethodThe convenience sampling technique is used to collect primary data via an online questionnaire. The respondents are 104 students of the Faculty of Islamic Studies, Universitas Islam Indonesia (UII), one of the internal stakeholders at UII. The method of data analysis is PLS-SEM using the SEMinR package in R software.ResultsThis study found that social influence and price values significantly affect the UII students' interest in donating through digital payments at LAZIS Unisia, while the rest of the independent variables are not. This study also found that intention significantly relates to actual behavior. Respondents outside the university also need to be considered for similar research. ImplicationsThe results of this study can be suggestions for LAZIS Unisia to improve engagement on donation from stakeholders in UII.Originality/NoveltyThis study is a pioneer in understanding the stakeholders' intention, especially students as internal stakeholder, to donate through digital payment at the stakeholders' institution. In addition to the UTAUT2 model, this study adds brand awareness and perceived security as independent variables.